Adaptive Power Factor Regulation under Asymmetrical and Non-Sinusoidal Grid Condition with Distributed Energy Resource - Bonaldo, Jakson Paulo (2021)
Active and reactive power regulation, unbalanced current compensation, and harmonic current mitigation are the most significant functionalities typically embedded to a three-phase multifunctional grid-connected inverter. However, a vital control feature minimally addressed in the literature is the capability to adjust the grid power factor to the minimum value required by standards or grid codes. Hence, this paper presents an adaptive compensation approach to perform dynamic power factor regulation under varying power demand and unpredictable energy generation, also withstanding non-ideal voltage conditions. To demonstrate such an approach, a global power factor definition is first introduced, being validated upon bidirectional power flow conditions and under unbalanced and distorted voltages. Secondly, a simple algorithm is devised to attain scaling coefficients used on compensation purposes, allowing to instantaneously weigh up reference control signals to track a desired grid-side power factor value. As a result, the strategy can be used to retrofit the controllers of grid-connected inverters with little effort, limiting distribution losses and improving power quality. Simulations and analyses of a representative real study case are conducted to illustrate how the proposed approach copes with unpredictable distributed energy resources and variable load demands. Moreover, experimental results considering a grid-connected inverter prototype are shown to validate the feasibility of the control approach to real-life implementations.